83.0k views
4 votes
Given z (x)=15x-x^2+3

Given z (x)=15x-x^2+3-example-1

1 Answer

3 votes

Answer:


z(x - 1) = -x^2 + 17x - 13

Explanation:

We are told that:


z(x)= 15x - x^2 + 3,

and told to find an expression for
z(x - 1).

In order to find
z(x - 1), we have to replace
x in the definition of
z(x) with
(x-1):


z(x - 1) = 15(x -1) - (x - 1)^2 + 3

Now we can simplify:


z(x-1) = 15x - 15 - (x - 1)^2 + 3 [Distributing 15 into the first brakets]


z(x-1) = 15x - 15 - (x^2 - 2x + 1) + 3


z(x-1) = 15x - 15 - x^2 + 2x - 1 + 3 [Distributing the minus sign]


z(x - 1) = 17x - x^2 -13 [Combining like terms]


z(x - 1) = -x^2 + 17x - 13

Therefore, the first option is the correct one.

User Stelian
by
5.8k points